2023
DOI: 10.3390/v15122432
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Combination Antiretroviral Treatment on Liver Metabolic Health in HIV-Infected Persons

Michał Biały,
Marcin Czarnecki,
Małgorzata Inglot

Abstract: In the last three decades, there has been a considerable improvement in human immunodeficiency virus (HIV) therapy. Acquired immunodeficiency syndrome (AIDS) is no longer a common cause of death for people living with HIV (PLWH) in developed countries, and co-infections with hepatitis viruses can be effectively managed. However, metabolic syndrome and metabolic dysfunction-associated steatotic liver disease (MASLD) are emerging threats these days, especially as the HIV-positive population gets older. The facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 65 publications
(116 reference statements)
2
1
0
Order By: Relevance
“…However, one year after starting the treatment, significant differences are observed in the increase in transaminases and ALP. Through these results, we reinforce the findings of other studies [ 20 , 21 , 22 ] that demonstrate that the new generation therapy affects liver function less than the older generation therapy.…”
Section: Discussionsupporting
confidence: 90%
“…However, one year after starting the treatment, significant differences are observed in the increase in transaminases and ALP. Through these results, we reinforce the findings of other studies [ 20 , 21 , 22 ] that demonstrate that the new generation therapy affects liver function less than the older generation therapy.…”
Section: Discussionsupporting
confidence: 90%
“…Our research observed that lipid pro le deterioration was particularly pronounced in measurements taken within the rst 24 months. The study's subgroup analyses showed that TAF and BIC therapies had the most detrimental impact on cholesterol levels [33]. Our study also indicates that lipid deterioration was particularly pronounced in measurements taken within the rst 24 months.…”
Section: Discussionsupporting
confidence: 49%
“…Our study also indicates that lipid deterioration was particularly pronounced in measurements taken within the rst 24 months. Another study highlighted that over the years, switching from TDF to TAF and especially using INSTI combinations could lead to a cascade of metabolic disorders, including metabolic syndrome, fatty liver, and eventually insulin resistance [34]. The elevation in ALT observed in cases using TAF-based combinations could be associated with hepatosteatosis.…”
Section: Discussionmentioning
confidence: 99%